A Capital Opportunity: Creating a New Zealand Jurisprudence in Public and International Law - Baragwanath, David (Victoria University of Wellington Law Review, 2010)
This is the written form of a lecture delivered at the Law Faculty on 28 April 2010 by Justice Baragwanath as part of a series of lectures delivered the various New Zealand law schools, to mark the judge's retirement from the New Zealand Court of Appeal. In this lecture the judge argues for the creation of a New Zealand public law that both acknowledges the special nature of New Zealand society and recognises the global context within which all New Zealand law must now fit and to some extent must be judged.